From fear to belonging: Learning experiences of Muslim minority international students in Islamic education in Indonesia - Ismail, Ismail; Suja’i; Ridwan, Mohammad; Siswayanti, Novita; Masfiah, Umi (Journal of International Students, 2026)
This study explores the academic shock experienced by international students from Muslim minority countries in Asia—Thailand, China, and Cambodia—who enrolled in an undergraduate Islamic Education program in Indonesia. Using a qualitative narrative inquiry approach, data were collected through unstructured interviews with participating students. Findings reveal a significant shift in students’ perceptions during their studies. Initially influenced by media portrayals of terrorism and conflict, many students arrived with fear and uncertainty about studying in Indonesia. Over time, however, their academic and social experiences challenged these assumptions. Through inclusive interpretations of Islam, local cultural engagement, and dialogical learning, students encountered values of tolerance, hospitality, and mutual respect. This transformation encouraged them to promote religious moderation, interfaith dialogue, and humanistic education upon returning to their home countries. The study extends the concept of academic shock across intellectual, psychosocial, and spiritual dimensions.